Development of Class V Literacy and Numeration Questions Based on ESD on The Theme The Environment is Our Friend at SDN 2 Kuta - Indraswati, Dyah; Nisa, Khairun; Jiwandono, Ilham Syahrul; Rahmatih, Aisa Nikmah; Putri, Hikmah Ramdhani (Departemen Pendidikan Guru Madrasah Ibtidaiyah Fakultas Tarbiyah dan Keguruan Universitas Islam Negeri Antasari Banjarmasin, 2023)
This research is motivated by the idea that the implementation of Education for Sustainable Development (ESD)-based learning can be a solution for teachers to instill awareness of the importance of preserving the environment. The purpose of this study was to produce test questions based on ESD literacy and numeracy based on the environmental theme of our friends, the sub-theme of humans and the environment. The research method used is Design Based Research (DBR) with the Reeves Model stages. The design of the test questions of 30 multiple choice questions was validated by 2 teachers. The validation results were then used as a guideline for revising which was then continued with trials on fifth grade students at SDN 1 Kuta. The results of the data analysis showed that based on the different test with Ms Excel, there were 2 questions that were rejected, 11 questions that were accepted and 17 questions that needed to be revised. Based on the results of the analysis of the level of difficulty, there are 3 questions in the easy category, 6 questions in the difficult category and 21 questions in the medium category. Based on the results of the validity analysis of the 30 questions tested, 15 questions were declared valid and 15 questions were declared invalid. Furthermore, valid questions were used as evaluation questions for fifth grade students at SDN 2 Kuta.